Retrospective study of tissue transglutaminase antibody levels in celiac disease-suspected patients at tertiary care hospital in Uttarakhand - Swati Rajput; Rohit Gupta; Itish Patnaik; Yogesh Bahurupi; Prashant Kumar; Kiran Meena; Nowneet Kumar Bhat; Satyavati Rana (Acta Medica International, 2021)
Introduction: Celiac disease (CD) is a chronic gastrointestinal disorder arising due to gluten sensitivity in susceptible individuals. In India, one person per 100 is suffering from this disease. CD has been reported more in high wheat-consuming areas like northern India. However, the incidence of CD in patients attending tertiary care hospital of Uttarakhand has not yet been reported. Therefore, this study was planned. Materials and Methods: A retrospective study with 603 patients was done at AIIMS Rishikesh in Biochemistry Department. These patients were screened for CD by tissue transglutaminase antibodies (ttgA) levels using enzyme-linked immunosorbent assay method. Percentage of levels of ttgA <4 U/ml (normal value) and >4U/ml in male, female adults, and children was calculated. Chi-square test was applied to compare results. Results: Out of 603 patients, 23 (3.81%) had abnormally raised ttgA levels (>4 U/ml). Percentage (15.18%) of ttgA levels in male children was significantly (P = 0.01) higher than 2.56% in female children. Mean + standard deviation (SD) of normal and abnormal ttgA levels in patients was 1.17 + 0.45 versus 66.81 + 34.80 U/ml, respectively. Mean + SD of abnormal ttgA levels in children and adults was 72.84 + 41.91 versus 32.38 + 24.75 U/ml, respectively. There was a statistically significant difference in abnormal ttgA levels among children and adults with children predominantly being higher (P = 0.0235). Conclusion: This study shows that levels of ttgA suggestive of CD in children are higher as compared to adults and more in males than females attending tertiary care hospital of Uttarakhand.